ANALISIS PELAKSANAAN RITUAL ADAT BATALAH PADA SUKU DAYAK KANAYATN DIDUSUN OTO LEDAKNG KABUPATEN LANDAK - Nikolaus Nikolaus; Imran Imran; Ika Rahmatika Chalimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research aims to describe the implementation of traditional Batalah rituals in the Kanayatn Dayak Tribe in Oto Ledakng Hamlet, Landak Regency. This research used a qualitative method with a descriptive-ethnographic approach. The data collection technic used a observation, interviews and documentation. The data collection tools used a observation guideline, interview guideline and documentation tools. The data analysis technic used a data reduction, data presentation and conclusion drawing. The testing of data validity used a source triangulation and a technical triangulation. The results of this research showing, (1) the process of the traditional Batalah ritual consists of two stages, the first is preparing the equipment for the ritual, before the traditional Batalah ritual carried out. Second, the day of the implementation of the traditional Batalah ritual which is carried out in the Nyangahant way. Nyangahant is divided into two, namely raw Nyangahant and cooked Nyangahant, after finishing the Nyangahant the next stage is bathing the baby, Ngaramak Suba, and eating together. (2) the function of the traditional ritual of Batalah in the Kanayatn Dayak Tribe in Oto Ledakng Hamlet, Sengah Temila District, Landak Regency is to give a name to a newborn child by means of a traditional ritual that will become the name or identity of the baby for life. (3) the values contained in the traditional Batalah rituals of the Kanayant Dayak Tribe are the value of mutual cooperation, religion and cleanliness.